Allelopathy in the tropical alga Lobophora variegata (Phaeophyceae): mechanistic basis for a phase shift on mesophotic coral reefs?. Issue 3 (25th March 2014) - Slattery, Marc; Lesser, Michael P.; Dunton, K.
<x xml:space="preserve">Abstract</x> Macroalgal phase shifts on Caribbean reefs have been reported with increasing frequency, and recent reports of these changes on mesophotic coral reefs have raised questions regarding the mechanistic processes behind algal population expansions to deeper depths. The brown alga Lobophora variegata is a dominant species on many shallow and deep coral reefs of the Caribbean and Pacific, and it increased in percent cover (>50%) up to 61 m on Bahamian reefs following the invasion of the lionfish Pterois volitans. We examined the physiological and ecological constraints contributing to the spread of Lobophora on Bahamian reefs across a mesophotic depth gradient from 30 to 61 m, pre‐ and post‐lionfish invasion. Results indicate that there were no physiological limitations to the depth distribution of Lobophora within this range prior to the lionfish invasion. Herbivory by acanthurids and scarids in algal recruitment plots at mesophotic depths was higher prior to the lionfish invasion, and Lobophora chemical defenses were ineffective against an omnivorous fish species. In contrast, Lobophora exhibited significant allelopathic activity against the coral Montastraea cavernosa and the sponge Agelas clathrodes in laboratory assays. These data indicate that when lionfish predation on herbivorous fish released Lobophora from grazing pressure at depth, Lobophora expanded its benthic cover to a depth of 61 m, where it replaced the dominant coral and sponge species. Our results suggest that this chemically defended alga may out‐compete these species in situ, and that mesophotic reefs may be further impacted in the near future as Lobophora continues to expand to its compensation point.